Affirmative discourse intervention: A framework for re-democratising engagement with education policy discourse. (June 2022) - Hunkin, Elise; Kilderry, Anna; Nolan, Andrea
In recent times, education policy and reform discourses have become increasingly politicised by neo-liberalism, with critical policy methodologies struggling to catch up. Critical policy sociologists have noted that critical commentaries rarely succeed in changing or impacting dominant education policy pathways. This article presents a framework for critical engagement in education policy drawing on Foucauldian notions of governmentality, with the aim to imagine a path to policy discourse intervention, or truth-telling. The 'affirmative discourse intervention' model comprises three interrelated processes to engage and respond to discourse as a function of governmentality: discourse recognition, discourse disruption and discourse agency. The article outlines the affirmative discourse intervention model and its theoretical underpinnings, then draws on data from the recent and ongoing Australian early childhood quality reform policy to illustrate the affirmative discourse intervention processes in application. The final section offers possibilities that emerge when re-imagining discourse agency in early childhood education and invites further commentary.